Accumulation of macronutrients in cv. 'Astrus' cabbage as influenced by nitrogen dose and plant population - Cecilio Filho, Arthur B. [UNESP]; Cavarianni, Rodrigo L. [UNESP]; Nowaki, Rodrigo H. D. [UNESP] (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2016)
The influence of plant population (31,250 and 46,875 plants ha(-1)) and nitrogen doses (0, 100, 200, and 300 kg ha(-1)) on the accumulation of macronutrients by cabbage plants was studied in Jaboticabal, Brazil, from February 18 to June 2, 2004. The experimental design was a randomized complete block in a 2 x 4 factorial scheme, with three replications. Differences in the amount of macronutrients accumulated by cabbage as function of N dose and plant population, were observed. The largest amounts of macronutrients were detected at the end of the plant cycle when the plant population was the lowest. The amounts of N, P, K, and S were not significantly different when the N dose was increased from 100 to 300 kg ha(-1). The accumulated amounts of Ca and Mg were not significantly different when the N dose was increased from 200 to 300 kg ha(-1). The decreasing sequence of macronutrient extraction (Ca, N, K, Mg, P, and S) was not altered by the treatments. The period from 40 to 60 days after transplantation was responsible for half of the macronutrient accumulation by the cabbage plants.
Keywords: Brassica oleracea var. capitata; spacing; uptake nutrients